Determination of anthocyanins and anthocyanidins in the wild grape (Vitis sylvestris Gmelin) by high-performance liquid chromatography-diode array detection (HPLC-DAD) - Karaaslan-Ayhan, Nagihan; Yaman, Mehmet (Taylor & Francis Inc, 2022)
The determination of anthocyanins and anthocyanidins in wild grapes (Vitis sylvestris Gmelin) from Tunceli-Turkey are reported together with the influence of the extraction conditions on the results. Representative sets of anthocyanins (delphinidin-3-o-glucoside, cyanidin-3-o-glucoside, pelargonidin-3-o-glucoside, malvidin-3-o-glucoside) and anthocyanidins (delphinidin, cyanidin, pelargonidin, malvidin) were simultaneously determined by high performance liquid chromatography with diode array detection (HPLC-DAD). The extraction conditions including the solvent type, extraction time and liquid:solid ratio (v:w) were optimized. The anthocyanin and anthocyanidin contents changed significantly depending on the extraction conditions. Malvidin-3-o-glucoside was identified to be the primary compound.
Keywords: Anthocyanin; anthocyanidin; wild grape; extraction condition; high-performance liquid chromatography; diode array detection